Differences in neuromuscular strategies between landing and cutting tasks in female basketball and soccer athletes - Cowley, H. R.; Ford, K. R.; Myer, G. D.; Kernozek, T. W.; Hewett, T. E. (Journal of Athletic Training, 2006)
Context: High school female athletes are most likely to sustain a serious knee injury during soccer or basketball, 2 sports that often involve a rapid deceleration before a change of direction or while landing from a jump.